Analisis Faktor Employee Agility terhadap Kesiapan Penerapan Rekam Medis Elektronik di Rumah Sakit Pertamina Bintang Amin - Liasari, Deny Eka; Farich, Achmad; Angelina, Christin; Sudirahayu, Ika; Rachmawati, Rachmawati (Universitas Malahayati, 2024)
ABSTRACT The use of RME will be realized optimally if organizations and health workers are ready to operate it. Unpreparedness in using RME can cause a number of problems, even making health workers lose interest in using it. As a result, RME implementation is at risk of failure and has the potential to have a negative impact on patient care because vital clinical and administrative data can be lost. The implementation of Electronic Medical Records (RME) in hospitals is an important element in Indonesia's health strategy which aims to improve the efficiency and accuracy of health services. Therefore, this research focuses on analyzing employee agility factors on readiness to implement electronic medical records at Pertamina Bintang Amin Hospital in 2024. The research method used is quantitative with a cross-sectional design. A sample of 157 respondents, who are healthcare workers responsible for implementing EMR, was selected using proportional random sampling techniques. The dependent variable assessed is readiness to implement RME and the independent variable is personality; work experience, personal abilities, environment and social. The research results showed that the independent variables related to EMR implementation readiness are work experiencce (pv:0,012), personal abilities (pv:0,000), environment (pv:0,000), and sosial (pv:0,000). The most dominant influencing factor is personal abilities with an 21,189 (95% CI: 4,249 – 105,656) which means that individuals whose abilities are good are 21 times more prepared . It is hoped that these results can become a reference for hospital management to utilize external resources such as RME vendors, technology consultants, and government or regulatory agencies to support RME implementation. Keywords: Electronic Medical Record, Implementation, Readiness, Employee Agility, Hospital ABSTRAK Penggunaan RME akan terwujud secara optimal apabila organisasi dan petugas kesehatan telah siap dalam mengoperasikannya. Ketidaksiapan dalam penggunaan RME dapat menimbulkan sejumlah masalah, bahkan membuat petugas kesehatan kehilangan minat untuk memanfaatkannya. Akibatnya, implementasi RME berisiko mengalami kegagalan dan berpotensi memberikan dampak negatif pada pelayanan pasien karena data klinis dan administratif yang vital dapat terhapus. Penerapan Rekam Medis Elektronik (RME) di rumah sakit adalah elemen penting dalam strategi kesehatan Indonesia yang bertujuan untuk meningkatkan efisiensi dan akurasi layanan kesehatan. Oleh karena itu, penelitian ini memfokuskan pada analisis faktor employee agility terhadap kesiapan penerapan rekam medis elektronik di Rumah Sakit Pertamina Bintang Amin Tahun 2024. Metode penelitian yang digunakan kuantitatif dengan rancangan cross sectional. Sampel yang diambil sebanyak 157 responden dan merupakan petugas kesehatan yang akan mengimplementasikan RME dengan teknik proportional random sampling. Variabel dependen yang dinilai yaitu kesiapan penerapan RME dan variabel independen berupa kepribadian; pengalaman kerja, kemampuan diri, lingkungan, dan sosial. Hasil penelitian didapatkan variabel independen yang berhubungan dengan kesiapan penerapan RME adalah pengalaman kerja (pv:0,012), kemampuan diri (pv:0,000), lingkungan (pv:0,000) dan sosial (pv:0,000). faktor paling dominan yang berpengaruh berupa kemampuan diri dengan Odd Ratio (OR) 21,189 (95% CI: 4,249 – 105,656) yang artinya individu yang kemampuan dirinya baik 21 kali lebih siap. Hasil ini diharapkan dapat menjadi acuan manajemen rumah sakit untuk memanfaatkan sumber daya eksternal seperti vendor RME, konsultan teknologi, dan lembaga pemerintah atau regulasi untuk mendukung penerapan RME. Kata Kunci: Kesiapan, Penerapan, Rekam Medis Elektronik, Employee Agility, Rumah Sakit